Mitochondrial genome of Dinophilus gyrociliatus (Annelida: Dinophilidae). Issue 2 (12th December 2017) - David, Kyle T.; Halanych, Kenneth M.
Abstract: Here we report the 14, 678 bp mitochondrial genome of the annelid Dinophilus gyrociliatus, the first mitochondrial genome from Dinophilidae. We recovered 13 protein-coding genes, two rRNA, and 21 tRNA, the order of which is different from other annelid species. Interestingly, trnS1 was not recovered. The GC% across the genome was 34.20%.